2017
DOI: 10.1007/s00774-017-0866-z
|View full text |Cite
|
Sign up to set email alerts
|

YC-1 alleviates bone loss in ovariectomized rats by inhibiting bone resorption and inducing extrinsic apoptosis in osteoclasts

Abstract: Osteoporosis is a major health problem in postmenopausal women and the elderly that leads to fractures associated with substantial morbidity and mortality. Current osteoporosis therapies have significant drawbacks, and the risk of fragility fractures has not yet been eliminated. There remains an unmet need for a broader range of therapeutics. Previous studies have shown that YC-1 has important regulatory functions in the cardiovascular and nervous systems. Many of the YC-1 effector molecules in platelets, smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Consistent with previous studies, we found that calcitonin treatment not only decreased the levels of serum bone resorption markers (i.e., TRAP5b and CTX-1) in OVX rats ( Figure 2 ) ( 14 , 15 ) but also led to increased levels of bone formation markers (i.e., osteocalcin and P1NP) in OVX rats ( 11 , 15 ). Because Wnt10b has recently been identified as a clastokine able to increase osteoblast activity, the finding that increased Wnt10b serum levels are correlated with osteocalcin and Wnt10b expression in bone marrow in calcitonin-treated OVX rats ( Figure 3 ) implies that Wnt10b may be involved in the effects of osteoclasts coupling to osteoblasts.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, we found that calcitonin treatment not only decreased the levels of serum bone resorption markers (i.e., TRAP5b and CTX-1) in OVX rats ( Figure 2 ) ( 14 , 15 ) but also led to increased levels of bone formation markers (i.e., osteocalcin and P1NP) in OVX rats ( 11 , 15 ). Because Wnt10b has recently been identified as a clastokine able to increase osteoblast activity, the finding that increased Wnt10b serum levels are correlated with osteocalcin and Wnt10b expression in bone marrow in calcitonin-treated OVX rats ( Figure 3 ) implies that Wnt10b may be involved in the effects of osteoclasts coupling to osteoblasts.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, evidence has revealed an inhibitory effect of NO on osteoclasts at low concentrations. NO has been reported to increase osteoclast and osteoclast precursor cell apoptosis (101,(130)(131)(132). A novel NO donor, nitrosyl-cobinamide (NO-Cbi), has been found to reduce the RANKL/OPG gene expression ratio or directly inhibit osteoclast differentiation in vitro and in vivo (133).…”
Section: Osteoclastsmentioning
confidence: 99%
“…Wang and his colleagues evidenced that YC-1 inhibited bone resorption and induced extrinsic apoptosis of osteoclasts to reduce bone loss, which implied that YC-1 has potential application for use as an antiresorptive drug in postmenopausal osteoporosis [102]. Besides, YC-1 and its derivatives also have been mentioned to improve hepatic fibrosis, which mechanisms may be caused by inhibiting liver neutrophil infiltration as well as decreasing in TNF-α signaling and macrophage aggregation [103,104].…”
Section: Other Activitiesmentioning
confidence: 99%